The levels and trends of cancer incidence in the elderly population at national and sub-national scales in Iran from 1990 to 2016 - Zahra Shokri Varniab; Sahar Saeedi Moghaddam; Ashkan Pourabhari Langroudi; Sina Azadnajafabad; Seyede Salehe Mortazavi; Ali Sheidaei; Kimiya Gohari; Yosef Farzi; Zeinab Shirzad Moghaddam; Hanye Sohrabi; Mohsen Shati (Cancer Reports, 2024)
Cancer is most commonly associated with aging. It is necessary to gain a better understanding of cancer's trend and distribution among elderlies and provide comprehensive cancer care for this population. The aim of the current study was to show the trends in cancer incidence focusing on the population aged 60+ from 1990 to 2016 in Iran. We used the dataset of the Iran Cancer Registry to estimate cancer incidences by sex, age, province, and year. In order to account for incomplete data we used a two-stage spatiotemporal model along with random intercept mixed effect models. We calculated annual age-standardized incidence rates (ASIRs) for age groups 60+ and 5-interval age groups. There was an increasing trend of 25.3% to 936.9% (95% uncertainty interval: 769.6–1141.8) in ASIR in the elderly in 2016. ASIR of all cancers were 889.7 (731.3–1083.6) in women and 988.1 (811.1–1205) in men in 2016, per 1000.167em000 respectively, which had an increasing trend comparing 1990. Skin, breast, and stomach cancers in women and prostate, skin, and stomach cancers in men were the most common types in 2016. All the most incident cancer subtypes underwent an increasing trend in both sexes, except for the bladder, esophageal, and skin cancers which almost had a similar level in 1990 and 2016. Most provinces had an increasing trend in ASIR in all cancers combined from 1990 to 2016 except Zanjan with a decreasing trend. Regarding the persistent increasing trend of most elderly cancers' incidence, this is crucial for policymakers to establish preventive plans, determine proper resource allocation, and develop specific treatments for elderly cancer patients.
Keywords: 330; elderly; epidemiology; geriatrics; incidence; neoplasms